(3ecGJHI Edi Cgd GdcOjI GdHjVGAs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj,J (B433 (3g` s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG hMOg GdefLR dYHOg GdGeGe GdgGOi hYOg Edi GdcOjI GdHjVGA GdYGdjf CgdgG s
(3BNQgG (B:s
(3JOaY Edjg cJHce aEfgG hGUdg Ydi jOg acJH bGFe GdReGf HNWg hGdMeO dehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdGeJgG HGdMeQIs
(3QSGdI ef QSGFd GdOQhR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B79s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds